Food and non-food prices nexus in developing economies: Disaggregated panel data analysis - Mujahid Zaman; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
In this paper, an attempt has been made to examine a new transmission mechanism of inflation that is effect of food prices on non-food prices. The panel generalized method of moment (GMM) has been employed on the panels of 47 developing countries disaggregated by income, i.e. low-income, lower-middle income and upper-middle income countries. The data-set covers the time period of 2000 to 2014. The panel Granger causality tests like error correction model, panel Stacked and Dumitrescu Hurlin test of causality are also employed to see the direction of causality between food prices and non-food prices. The results of panel GMM estimation indicate that food prices positively affect non-food prices in all the income groups of economies. The causality direction is also found from food prices to non-food prices in these groups of economies. It concludes that inflation transmission mechanism of food prices to non-food prices exists in developing countries. For policy making, it is suggested that any attempt to control inflation in developing economies, one component of anti-inflationary policy should be to control the food prices.
Keywords: 330; Food prices; Non-food prices; Granger causality; Inflation transmission; Money supply